Substance Use in Mild-COVID-19 Patients: A Retrospective Study - Ismael, Flavia; Zaramella, Beatriz; Battagin, Tatiane; Bizario, João C. S.; Gallego, Júlia; Villela, Victoria; de Queiroz, Lilian Bezerra; Leal, Fabio E.; Torales, Julio; Ventriglio, Antonio; Marziali, Megan E.; Gonçalves, Priscila D.; et al. (Frontiers in Public Health, 2021)
Background: There is a need for prospective studies investigating substance use variations in mild COVID-19 patients. These individuals represent the majority of patients affected by the disease and are routinely treated at home, facing periods of quarantine. Methods: This was a retrospective cohort study. All people who tested positive for COVID-19 and classified as mild cases (i.e., no alarm sign/symptom, no need for in-person consultation) during the treatment in the public health system of a Brazilian city with around 160,000 inhabitants were monitored by phone for all the COVID-19 symptoms listed by the Centers for Disease Control and Prevention (CDC) during the active phase of the disease (i.e., no longer experiencing symptoms, up to 14 days in mild cases). After this phase (median = 108 days after intake, IQR = 76–137), we asked these patients who were classified as experiencing mild COVID-19 (n = 993) about last-month substance use in three time-points: pre-COVID, just after COVID-19 acute phase (post-COVID acute phase) and in the period before survey (post-COVID follow-up phase). Results: The number of COVID-19 symptoms was not associated with pre- or post-infection substance use. Pre-COVID alcohol and non-medical benzodiazepine use were associated with specific COVID-19 symptoms. However, sensitivity analyses showed that such associations could be explained by previous psychiatric and medical profiles. Alcohol and tobacco use decreased and non-medical analgesics increased in the post-COVID acute phase. However, just alcohol use remained lower in the post-COVID follow-up period. Higher pre-COVID levels of tobacco and alcohol were associated with post-COVID follow-up cannabis and non-medical analgesic use, respectively. Non-medical benzodiazepine use had positive and negative bi-directional associations with cannabis and non-medical analgesic use, respectively. Conclusion: We were not able to find specific associations between substance use and COVID-19 symptomatology in the present study. Patients with mild COVID-19 should be monitored for substance use in the post-COVID-19 period, and preventive interventions for non-medical analgesic use should be implemented. Focused preventive interventions increasing the perceived risks of cannabis and non-medical benzodiazepine and analgesic use among people experiencing mild COVID-19 that reported previous substance use could be useful.